An example of accreditation applications of veterinary education in turkey within the frame of current european association of establishments for veterinary education (eaeve) parameters - Nigar Yerlikaya; Özgül Küçükaslan (Eurasian Journal of Veterinary Sciences)
Aim: Quality parameters are determined with accreditation standards in higher education institutes. EAEVE carries out international accreditation practices in our country. In this study, the last statuses of Turkish veterinary faculties in accreditation processes are evaluated as of December 2020. Besides, evaluation of the current status of Ankara University Faculty of Veterinary Medicine (AUFVM) in accordance with European System of Evaluation of Veterinary Training (ESEVT) 2019 Standard Operating Procedures (SOP) criterion is aimed as an example from Turkey. Materials and Methods: In this study, the accreditation status of veterinary faculties in Turkey are evaluated. The data of AUFVM is evaluated following EAEVE's current 2019 SOP criterion and found out that the faculty is insufficient for 7 out of 22 main indicators. Excel file provided by European System of Evaluation of Veterinary Training (ESEVT) is used to calculate of the last 3 years' data of the faculty. Results: As of December 20, there are 27 fully accredited veterinary schools out of 101 members of EAEVE. Accordingly, there are 3 approved faculties out of 13 member faculties of EAEVE in Turkey as of December 2020. AUFVM is identified as the first member and approved faculty of EAEVE. As an example of Turkey, AUFVM?s data is compared with foreign approved or fully accreditated veterinary schools and strengths and weaknesses are determined. Conclusion: This study has authentic value in terms of being the first study in Turkey according to the EAEVE's last criteria (2020) as a quality commitment of accreditation processes. Consequently, following the latest accreditation criterion for all veterinary faculties in Turkey besides with novel researches is thought to be important in achieving international standardization of veterinary education.